Risywah in the Perspective of Islamic and Positive Law - Irmayadi Sastra (Tradition and Modernity of Humanity, 2024)
Risywah is strictly prohibited in Islamic law and positive law in Indonesia. This action cannot be separated from human behavior or attitudes in which there are always evil actions or intentions. Where someone will commit theft or bribery to further their interests, this act is more identically carried out by unscrupulous government officials in order to fulfill their needs or the interests of their group. We can find these actions in everyday life where sinful actions are carried out by anyone who wants to own something that is not rightfully theirs. Thus, not only does this theft and bribery have a negative impact on the perpetrator, it also has a detrimental impact on society.